THE SEASONAL ABUNDANCE OF SYNANTHROPIC FLY POPULATIONS IN TWO SELECTED FOOD OUTLETS IN PULAU PINANG, MALAYSIA - Nurita Abu Tahir,; Abu Hassan Ahmad,; Nur Aida Hashim,; Norasmah Basari,; Che Salmah Md Rawi, (Tropical Life Sciences Research, 2007)
The seasonal abundance study of adult synanthropic flies in two selected food outlets was conducted from July 2003 to July 2004. The two urban locations were a cafeteria in the Universiti Sains Malaysia (USM) main campus and an adjacent restaurant. Four synanthropic flies were identified from both study sites and they were Musca domestica (house fly), Musca sorbens, Chrysomya megacephala and Lucilia cuprina. The off-campus restaurant had a significantly higher (p < 0.05) fly abundance than the university cafeteria and the dominant fly species at both sites was the M. domestica. The highest fly abundance recorded at both sites was in April 2004. Total fly abundance was lowest in the university cafeteria and in the off-campus restaurant in March 2004 and October 2003 respectively. Kajian kelimpahan bermusim lalat sinantrofik dewasa dijalankan dari Julai 2003 sehingga Julai 2004 di sebuah kafeteria di kampus induk Universiti Sains Malaysia (USM) dan di sebuah restoran di luar kampus. Spesies yang telah dikenal pasti ialah Musca domestica, Musca sorbens, Chrysomya megacephala dan Lucilia cuprina. Restoran di luar kampus mempunyai kelimpahan lalat yang secara signifikannya lebih tinggi (p < 0.05) berbanding kafeteria universiti dengan spesies lalat yang dominan di kedua-dua lokasi ialah M. domestica. Kelimpahan lalat paling tinggi direkodkan di kedua-dua lokasi kajian pada April 2004. Kelimpahan lalat paling rendah di kafeteria universiti dan di restoran luar kampus masing-masing pada Mac 2004 dan Oktober 2003.